Tetralogy of Fallot with aortic stenosis and common arterial trunk: Is there a morphological overlap? - Saikiran Kakarla; Deepa Sasikumar; Anoop Ayyappan (Wolters Kluwer Medknow Publications, 2023)
Tetralogy of Fallot with aortic stenosis is an extremely rare entity which bears some morphological similarities with the common arterial trunk. Through two illustrative cases of TOF with aortic stenosis we describe the shared anatomical peculiarities of the two anomalies with a review of the possible genetic and developmental factors responsible for the association.